Pengaruh Pendapatan Asli Daerah (PAD), Dana Perimbangan, dan Pengeluaran Bidang kesehatan terhadap Indeks Pembangunan Manusia (IPM) Kabupaten Jombang Tahun 2007-2021 - Nugroho, Moch Erik; Hendrati, Ignatia Martha (Universitas Batanghari Jambi, 2024)
The aim of the research is to analyze the influence of a region's original income, balancing funds and health expenditure on the human development index (HDI) in Jombang Regency during the period 2007 - 2021. Using the multiple linear regression method by carrying out the Best Linear Unbiased Estimation (BLUE) test, and analysis hypothesis testing. The results of this research concluded that simultaneously the human development index (HDI) in Jombang Regency during the 2007-2021 period was influenced by local original income (PAD), balancing funds and expenditure in the health sector. However, only partial balancing funds can influence the human development index in Jombang Regency during the 2007-2021 period.